PELATIHAN ASESSMEN PEMBELAJARAN BERBASIS QUIZIZZ PADA GURU UPTD SMP NEGERI 1 BARRU SEBAGAI EVALUASI PENILAIAN PEMBELAJARAN: Pelatihan Asesmen Pembelajaran Berbasis Quizizz - Nawir, Muhammad; Binti Hamid, Nurasyura; Mu'minang, Mu'minang; Nasir, Nasir (RAMBIDEUN : Jurnal Pengabdian Kepada Masyarakat, 2025)
This community service activity aimed to provide knowledge about optimizing the quizizz application service to teachers of UPTD SMP Negeri 1 Barru, which was held on October 9, 2024 in the Hall of SMP Negeri 1 Barru, Barru Regency, South Sulawesi. The training participants consisted of 64 teachers of SMP Negeri 1 Barru. This training was guided by the Quizizz Super Trainer, Mr. Jamal Passalowongi, S.Pd., M.Pd. The training methods used by the presenters were in the form of direction, questions and answers, direct practice in the field, and mentoring. The results obtained from this community service activity were that the training participants gave a positive response when taking part in the training, and the participants were very enthusiastic and there was an increase in teacher creativity in making learning evaluations using quizizz. However, the implementation of this activity also faced obstacles, such as limited technological infrastructure, internet access, and difficulty using the application's advanced features. For this reason, there should be further training on the use of quizizz features, so that teachers maximize the potential of this application in evaluation learning.